Detection of Necrosis by Release of Lactate Dehydrogenase (LDH) Activity - Chan, Francis Ka-Ming (2013)
Apoptosis and necrosis are two major forms of cell death observed in normal and disease pathologies. Although there are many assays for detection of apoptosis, relatively few assays are available for measuring necrosis. A key signature for necrotic cells is the permeabilization of plasma membrane. This event can be quantified in tissue culture settings by measuring the release of the enzyme lactate dehydrogenase (LDH). When combined with other methods, measuring LDH release is a useful method for detection of necrosis. In this chapter, we describe the step-by-step procedure for detection of LDH release from necrotic cells using a microtiter plate based colorimetric absorbance assay.